Analisis Peranan Pola Asuh Orang Tua Dalam Memotivasi Belajar Siswa - Nurfarija, Siti Isma; Chudari, Ima Ni'mah (Didaktika, 2022)
Parenting is the realization of the rules that parents set for students in everyday relationships. Good parenting can motivate students to keep growing. This research aims to find out the role of parenting parents and know the obstacles and solutions of parents when doing their parenting role in motivating student learning, using qualitative approaches and methods of literature studies. The results of analysis of several works of literature related to the issues studied regarding the role of parenting patterns carried out by parents, by applying authoritative or democratic parenting, which supports and frees students to explore things of interest, but with the control and control of people and in parental supervision. Another role of authorship is awareness in parents as the first educator, motivator, facilitator, and full responsibility as a guide who can direct students to the future in a good and right way. Then the obstacles of parents in motivating student learning are due to economic factors that are less fulfilled, so many parents pay less attention, and more time is spent on work, causing students to get less parental affection as well as the lack of awareness of parents in performing their role as the main educator. The solution carried out by parents is that parents realize the role of parenting and its responsibilities have an impact in fostering motivation in students to actively learn, by paying attention and supporting activities that students are interested in. As well as working with the school to discover the development of students and communities in the residential environment to form peaceful and supportive learning conditions for students.